2008
DOI: 10.1016/j.brainres.2008.04.080
|View full text |Cite
|
Sign up to set email alerts
|

Atypical functional lateralization of language in autism spectrum disorders

Abstract: Impaired language is a prominent behavioral marker of autism spectrum disorders (ASD), but its neurobiological underpinnings are incompletely understood. We studied letter and category fluency in 14 high functioning ASD individuals and 14 age-matched controls. Each fluency condition was compared to self-paced repetition of the word "nothing." Responses were recorded to monitor performance. In letter fluency, the ASD group had significantly greater activation than controls in the right frontal and right superio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
160
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(181 citation statements)
references
References 73 publications
19
160
1
1
Order By: Relevance
“…Present results point to increased MD along the left SLF and especially the left tSLF. Abnormal MD could result in reduced functional connectivity, a hypothesis consistent with previous fMRI findings of atypical right lateralization of the letter fluency task to the right inferior frontal lobe 35 and consistent with the theory of long-range underconnectivity in autism. 36 While connectivity inferences are beyond the scope of this analysis, it is perhaps worth considering a high value of MD as indicative of immature or abnormal WM development; therefore, high MD may well not be directly equivalent to hyperconnectivity and may, in fact, be associated with underdeveloped connectivity.…”
Section: Discussionsupporting
confidence: 87%
“…Present results point to increased MD along the left SLF and especially the left tSLF. Abnormal MD could result in reduced functional connectivity, a hypothesis consistent with previous fMRI findings of atypical right lateralization of the letter fluency task to the right inferior frontal lobe 35 and consistent with the theory of long-range underconnectivity in autism. 36 While connectivity inferences are beyond the scope of this analysis, it is perhaps worth considering a high value of MD as indicative of immature or abnormal WM development; therefore, high MD may well not be directly equivalent to hyperconnectivity and may, in fact, be associated with underdeveloped connectivity.…”
Section: Discussionsupporting
confidence: 87%
“…A relatively small sample of postmortem studies of individuals with autism has noted fewer neurons in the FG (van Kooten et al 2008). More common have been neuroimaging findings of hypo-activation in the FFA and the OFA in individuals with autism (Pierce et al 2001;Bookheimer et al 2008;Kleinhans, Muller et al 2008;Kleinhans, Richards et al 2008). While abnormal activation of the FFA has been attributed to atypical fixations onto faces in participants with autism (Dalton et al 2005), it may also arise from abnormal connectivity with the AMY (Schultz et al 2003;Kleinhans, Muller et al 2008;Kleinhans et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In line with the behavioral deficits observed in ASD, functional neuroimaging studies also report atypical activation of language relevant brain areas. For example, a growing number of fMRI studies have reported more bilateral or right-lateralized activity in adults (Kleinhans, et al, 2008a;Mason et al, 2008;Tesink et al, 2009) and children (Knaus et al, 2010;Redcay and Courchesne, 2008) with ASD. Although some studies have shown hyperactivation (Wang et al, 2006), others have reported hypoactivation (Gaffrey et al, 2007;Wang et al, 2007), and a few others have reported simultaneous decreased activity in frontal brain regions and increased activity in posterior temporal areas (Harris et al, 2006;Just et al, 2004) during basic language processing.…”
Section: Tom and Pragmatic Languagementioning
confidence: 99%